The Effects of BRICS and MATIK Countries on World Economy and Cointegration Analysis in the Long Term Relation with G-7 Growth Rates (1962-2012) - Bilal Kargi (Journal of Economics and Behavioral Studies, 2014)
In this article, long term data is analyzed for the total growth of the world economy and the growth of developed (G7) and of the rapid developing economies. BRICS countries are known countries with their meetings since 2008. Rapidly developing countries such as Mexico, Argentina, Turkey, Indonesia and Korea are defined as MATIK in this analysis except the countries for BRICS meeting. Especially, the basic hypotheses of this study is that BRICS+MATIK countries whose economic shares slowly increase were compared with G-7 and the global economy, i) Help of BRICS+MATIK economies rapidly increase for the growth rate of world economy: ii) They're the hypotheses that BRICS+MATIK economies are cointegrated with the growth of world economy in long term. In this way, it may be possible that the help of G-7 is compared with the help of BRICS+MATIK economies for the growth of world economy. The study uses the annual data of the 1962-2012 periods. Time series analysis is used to test the hypotheses. The most important finding is that BRICS+MATIK economies affect the growth rate of world economy, and it constantly increases as statistic according to the help of G-7.The result has been acquired that World, G-7, and BRICS+MATIK economies cointegrated in the long term.
Keywords: O40; O57; C22; 330; Economic Growth; BRICS and MATIK Countries; Developing Countries; World Economy